Comparison of traditional methods versus digital learning methods among undergraduate medical students in Pakistan - Shazia Fakhir Durrani; Ammara Hameed; Fatima Fakhir Musharraf (Journal of the Pakistan Medical Association, 2025)
Objective: To explore and compare the use of traditional and digital learning methods among undergraduate medical students. Method: The cross-sectional, qualitative, descriptive study conducted at the Bahria University of Health Sciences, Karachi, from June to December 2023, and comprised undergraduate medical, dental and allied health sciences students. Sample size was calculated using open epi and keeping confidence interval at 95%. Data was collected using in-depth interviews, and focus group discussions. Data was analysed using SPSS 22. Results: Of the 203 subjects, 48 were from the MBBS final year, 46 each from the fourth and third years, 30 from the second year, and 22 from the first year. Rest of them were from allied BDS, DPharm, DPT. Overall, N110 (54%) students favoured mixed methods of learning, N23 (12%) favoured digital alone, and N70 (34%) favoured the traditional methods. A total of 6 focus group discussions were held; N 146 (71.92%) medical students in five groups, and one group of N 57 (28.07%) dental, pharmacy and physical therapy students. The 3 main themes identified were digital methods, traditional methods and mixed methods of learning. Conclusion: The mixed method of learning was favoured by the majority of students. Digital platforms offer a variety of benefits that improve learning, while traditional methods remain valuable for comprehensive study and for building concepts. Key Words: Innovative digital platforms, digital learning, e-learning, traditional learning, medical studies, online learning.